2023
DOI: 10.1002/ejp.2098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high versus low cognitive load on the development of nociceptive hypersensitivity: The roles of sympathetic arousal, sex and pain‐related fear

Abstract: Background: According to limited-capacity theories of attention, less attentional resources remain available when engaging in a high-versus a low-demanding cognitive task. This may reduce the perceived intensity and the evoked cortical responses of concomitant nociceptive stimuli. Whether and how the competition for limited attentional resources between a cognitive task and pain impacts the development of long-lasting hypersensitivity is unclear.Methods: Eighty-four healthy participants were randomized into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…22,32,45,58,68 Importantly however, other recent studies that have used similar electrical stimulation protocols have found either modest or no modulation of SH. 4,18,48,66 This apparent difficulty may be due to the intense nature of the electrical stimulation and the large magnitude of SH that these procedures induce (eg, h p 2 5 0.47 in the current study). In addition, MFS stimulation induces the largest increase in perceived pinprick intensity compared with other frequencies.…”
Section: Effects Of Social Support On the Development Of Secondary Hy...mentioning
confidence: 78%
See 1 more Smart Citation
“…22,32,45,58,68 Importantly however, other recent studies that have used similar electrical stimulation protocols have found either modest or no modulation of SH. 4,18,48,66 This apparent difficulty may be due to the intense nature of the electrical stimulation and the large magnitude of SH that these procedures induce (eg, h p 2 5 0.47 in the current study). In addition, MFS stimulation induces the largest increase in perceived pinprick intensity compared with other frequencies.…”
Section: Effects Of Social Support On the Development Of Secondary Hy...mentioning
confidence: 78%
“…Most studies that have attempted to modulate SH by attentional effects have focused on the stimulation period. 22,48,65 Any distraction caused by the presence of the partner during the stimulation may have been minimized since providing ratings for the MFS stimulation would have kept participants' attention focused on the stimulation. This, however, remains a possibility that cannot entirely be excluded.…”
Section: Effects Of Social Support On the Development Of Secondary Hy...mentioning
confidence: 99%
“…Progress in this field has been made by investigating how psychological factors affect pain sensitization [5,6,16,22,29,42,44,45,55,64,66,72] and the subsequent development of secondary hypersensitivity -characterized by a long-lasting increased mechanical pinprick sensitivity in the area surrounding an injured or inflamed site [30,32,52,63]. For instance, Torta et al [64] found that performing an n-back (working memory updating) task during the application of electrocutaneous stimulation reduced consecutive mechanical hypersensitivity, while performing a Flanker (inhibition) task resulted in its enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…As the two tasks rely on different cognitive processes, it is challenging to directly compare the two solely based on their level of demand. To overcome this limitation, Meyers et al [45] compared two levels of difficulties of the n-back task (0-vs.2-back), but they did not observe a significant difference in secondary hypersensitivity. The same results were obtained in a follow-up study with a within-subjects design, including a control condition with no task [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation